2000
DOI: 10.1103/physrevlett.85.4245
|View full text |Cite
|
Sign up to set email alerts
|

Collisions between Metastable Hydrogen Atoms at Thermal Energies

Abstract: The complex interaction potentials arising in the approach of two metastable hydrogen 2s atoms are calculated and the cross sections for ionization, excitation transfer, and elastic scattering are predicted. The measured cross section for associative ionization at E = 4.1 meV equals 2x10(-15) cm (2). We calculate a total ionization cross section of 2x10(-13) cm (2), varying as E(-2/3) at higher energies. Thus it appears that dissociative ionization is the major ionization channel. We find also that double exci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 16 publications
2
16
0
Order By: Relevance
“…Previous calculations [48,50] have shown that the total ionization cross sections for the 1 + g and 3 + u states are 23E −2/3 and 15E −2/3 , respectively.…”
Section: Theorymentioning
confidence: 96%
See 4 more Smart Citations
“…Previous calculations [48,50] have shown that the total ionization cross sections for the 1 + g and 3 + u states are 23E −2/3 and 15E −2/3 , respectively.…”
Section: Theorymentioning
confidence: 96%
“…The full set of doubly excited molecular states converging to the H(n = 2) + H(n = 2) limit, the so-called Q(2) states, has been calculated over the entire range of internuclear distance R, and the associated energies and autoionization widths have been used to construct complex potential curves [49,51]. Multichannel scattering formulations have been used to calculate the collision cross sections at low translational energies [48,50]. At thermal energies, the tiny energy splitting between the 2s and 2p states may be ignored, and the contribution from the Coriolis force is also expected to be weak.…”
Section: Theorymentioning
confidence: 99%
See 3 more Smart Citations